Economic evaluation of user-fee exemption policies for maternal healthcare in Burkina Faso: evidence from a cost-effectiveness analysis - Nguyen, Hoa Thi; Torbica, Aleksandra; Brenner, Stephan; Kiendrébéogo, Joël; Tapsoba, Ludovic; Ridde, Valéry; De Allegri, Manuela (Value in health, 2020)
Objectives - The reduction and removal of user fees for essential care services have recently become a key instrument to advance universal health coverage in sub-Saharan Africa, but no evidence exists on its cost-effectiveness. We aimed to address this gap by estimating the cost-effectiveness of 2 user-fee exemption interventions in Burkina Faso between 2007 and 2015: the national 80% user-fee reduction policy for delivery care services and the user-fee removal pilot (ie, the complete [100%] user-fee removal for delivery care) in the Sahel region. - Methods - We built a single decision tree to evaluate the cost-effectiveness of the 2 study interventions and the baseline. The decision tree was populated with an own impact evaluation and the best available epidemiological evidence. - Results - Relative to the baseline, both the national 80% user-fee reduction policy and the user-fee removal pilot are highly cost-effective, with incremental cost-effectiveness ratios of $ 210.22 and $ 252.51 per disability-adjusted life-year averted, respectively. Relative to the national 80% user-fee reduction policy, the user-fee removal pilot entails an incremental cost-effectiveness ratio of $ 309.74 per disability-adjusted life-year averted. - Conclusions - Our study suggests that it is worthwhile for Burkina Faso to move from an 80% reduction to the complete removal of user fees for delivery care. Local analyses should be done to identify whether it is worthwhile to implement user-fee exemptions in other sub-Saharan African countries.
Gesehen am 30.04.2020